Hallmarks of glucocorticoid receptor condensates involvement in transcription regulation - Belén Benítez; Martin Stortz; María Cecilia De Rossi; Diego Martín Presman; Valeria Levi (iScience)
Summary: Several proteins necessary for mRNA production concentrate in intranuclear condensates, which are proposed to affect transcriptional output. The glucocorticoid receptor (GR) is a ligand-activated transcription factor that regulates the expression of hundreds of genes relevant to many physiological and pathological processes. As with all members of the steroid receptor family, GR forms condensates of unknown function. Here, we examine whether GR condensates are involved in transcription regulation using Airyscan super-resolution microscopy and nano-antibodies targeting initiation and elongating states of RNA polymerase II (Pol2). We observed subpopulations of GR condensates colocalizing with initiating and, surprisingly, elongating Pol2 foci. The analysis of GR mutants with different transcriptional outputs suggests a correlation between condensate formation capability and transcription initiation. Moreover, the number of GR molecules within initiation and elongation condensates appears to be linked to transcriptional activity. Taken together, our data suggests an involvement of GR condensates in transcription initiation and elongation.